Learning from the past: Supporting teaching through the Facing the Past History Project in South Africa - Tibbitts, Felisa (Prospects (Paris), 2006)
This article presents an innovative professional development project, "Facing the Past-Transforming Our Future," developed collaboratively by the Western Cape Educational Department, the Cape Town Holocaust Centre (CTHC), and the US-based teacher professional development organization Facing History and Ourselves (FHAO). "Facing the Past" was designed to support teachers in the introduction of the new South African history curriculum and, in particular, the 9th grade history requirement to teach human rights issues during and after the Second World War. Two major components of the 9th grade content framework are Nazi Germany and the Holocaust and apartheid South Africa. The South Africa programme mirrored FHAO's approach by creating teaching resources linked with the history curriculum and by providing sustained trainings, workshops, and ongoing classroom support. While meeting both the content and skill requirements of the new history standards, "Facing the Past" focuses on human behaviour and moral agency, infusing the use of narrative, interactive methods, and multi-media sources. Significantly, "Facing the Past" involves a systematic examination of human behaviour in Nazi Germany and the Holocaust as preparation for approaching the subject of apartheid in the classroom. This article draws on data collected for the year-long training programme carried out for two cohorts of teachers during the pilot period of 2003-2005. (Contains 3 notes.)